2005
DOI: 10.1254/jphs.sc0050046
|View full text |Cite
|
Sign up to set email alerts
|

Forced Exercise-Induced Flushing of Tail Skin in Ovariectomized Mice, as a New Experimental Model of Menopausal Hot Flushes

Abstract: Hot flushes are the most common complaint of menopausal women. In the present study, a new animal model of hot flushes was established. Tail skin temperature was measured with a thermo tracer after mice were subjected to a forced exercise task using a motor driven treadmill. In ovariectomized mice, forced exercise for 10 min was most effective in increasing tail skin temperature over that of sham-operated mice. This elevation was blocked by estradiol replacement (1 mg/kg per week for 3 weeks), suggesting that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Experiments on OVX rats make use of various triggers. Previous studies have found that OVX rats increased TST by the induction of stress with physical exercise [27]. Numerous studies have also reported that yohimbine administration causes hot flashes [28,29].…”
Section: Discussionmentioning
confidence: 94%
“…Experiments on OVX rats make use of various triggers. Previous studies have found that OVX rats increased TST by the induction of stress with physical exercise [27]. Numerous studies have also reported that yohimbine administration causes hot flashes [28,29].…”
Section: Discussionmentioning
confidence: 94%
“…Animal models of hot flushes have proved difficult to develop, but measurements of tail skin temperature in ovariectomized mice is an attractive model since it mirrors the peripheral vascular events seen in hot flushes (vasodilation in the skin leading to an increased temperature) and these effects can be blocked by estrogen supplementation (Kobayashi et al, 2000; Shuto et al, 2005). The model used in this study relies on flush-like events triggered by exercise on a treadmill.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological tools are available; antagonists toward CGRP-receptors have been developed and tested in human phase II and phase III studies, mainly for treatment of migraine (Villalon and Olesen, 2009; Bell et al, 2010; Hirsch et al, 2013) and MK-8825, a non-peptide CGRP receptor antagonist administered orally, has been shown to be active in rodents migraine (Villalon and Olesen, 2009). In order to find out if CGRP plays a causal role in hot flushes and if CGRP antagonism has therapeutic potential for this indication, we used the CGRP receptor antagonist MK-8825 in a previously reported mouse model of menopausal hot flushes (Shuto et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Ovariectomized, morphine-dependent rats exhibit rises in tail temperature during antagonist induced opiate withdrawal (44). Additionally, ovariectomized mice forced to exercise exhibit similar changes (45). Temperature effects in both models are dependent on ovariectomy and are tempered by exogenous estrogen.…”
Section: Discussionmentioning
confidence: 99%